A new species of the genus Lycodon (Boie, 1826) from the southwestern mountains of China (Squamata: Colubridae) - Vogel, Gernot; Luo, Jian (Zootaxa, 2011)
A new species of the genus Lycodon from the Gaoligong Mountains, Yunnan, China is described, Lycodon gongshan sp. nov. This species is similar to L. fasciatus, but differs in its longer tail, especially in males, and larger number of subcaudals, especially in females. The number of ventrals and maximum body size is greater in both sexes of the new species. From the Lycodon ruhstrati group, the new species differs in the colour of the belly and the dorsal bands. This new species seems to be endemic to Yunnan Province, People’s Republic of China. The holotype of Ophites fasciatus Anderson, 1879 appears to have been lost, so a neotype is designated in order to address the status of this taxon.